High-frequency ultrasound with superb microvascular imaging: a potential tool for ultrasound assessment in patients with giant cell arteritis - Skoog, Johan; Svensson, Christina; Eriksson, Per; Sjöwall, Christopher; Zachrisson, Helene (Frontiers in Medicine, 2024)
Objective The objective of this study was 2-fold: first, to evaluate whether superb microvascular imaging (SMI) could be used to visualize neovascularization in temporal arteries, and, second, to evaluate the diagnostic performance of high frequency ultrasound with SMI using an extended protocol in patients with suspected giant cell arteritis (GCA). Methods This retrospective study comprised 120 patients consecutively examined with an extended CDU protocol (temporal, facial, axillary, subclavian, brachiocephalic, and carotid arteries) between 2020 and 2022. Of all patients, 107 had no previous GCA diagnosis and 13 had a previous GCA diagnosis. SMI was used to evaluate neovascularization in the temporal arteries. Arteritis were characterized as low- or medium-echogenic, homogeneous wall thickening, with or without a positive compression sign in the temporal arteries. The Halo count, i.e., the number of temporal and axillary artery segments with signs of arteritis, was evaluated. The reference was clinically diagnosed GCA confirmed after ≥6-month follow-up. Results Of the eligible 107 patients with new suspected GCA, 33 (31%) received a clinical GCA diagnosis. Neovascularization was detected in 14 patients (43%). Patients with neovascularization displayed a higher halo count [median 6 (25th−75th percentile 4.75–7) vs. 3 (2-4-4), p = 0.005]. CDU of only the temporal arteries showed sensitivity and specificity (95% confidence intervals) of 94% (80–100%) and 100% (95–100%), respectively. The addition of extra-cranial arteries increased the sensitivity to 100%. Of the 13 patients investigated for suspected relapse, three had a clinically confirmed relapse. One of them displayed neovascularization together with other signs of inflammation. Conclusions We show for the first time that inflammatory neovascularization of the temporal arteries can be detected by SMI. Neovascularization is associated with a more-widespread cranial disease. The value of neovascularization should be further investigated, especially for the detection of GCA relapse.